MANUSKRIP ARAB DI NUSANTARA DALAM TINJAUAN LINGUISTIK KORPUS - Hizbullah, Nur; Suryaningsih, Iin; Mardiah, Zaqiatul (Arabi : Journal of Arabic Studies, 2019)
The history and development of Islam in Indonesia are enriched by the existence of manuscripts written in Arabic language or written in Arabic script, like Pegon or Jawi although they do not use Arabic. In the context of corpus linguistics, the manuscript is a proof of the existence and dynamics of real Arabic usage by Indonesian speakers. This paper describes several classifications of manuscripts written in Arabic and their urgency as the material of Arabic corpus data in Indonesia in the context of the development of multidisciplinary Arabic research. Furthermore, the manuscript will be mapped based on seven types of Arabic corpus in Indonesia. Based on the mapping, it is projected that the majority of Arabic manuscripts in the archipelago are categorized as a corpus of scientific works, the corpus of Islamic studies, and corpus of literary works. For this purpose, it is necessary to process those manuscripts into digital text material to be analyzed with corpus processing applications through three stages: image scanning, image conversion into text, and manual text verification.